G239 Validation of two risk stratification guidelines in a one year cohort of febrile admissions in paediatric oncology patients in a UK centre. (7th April 2014) - Arif, T; Sutcliffe, R; Hewitt, M; Wilne, S; Stokley, S; Boyer, H; Manning, K; Bambridge, O; Walker, DA
Abstract : Background: Febrile illnesses complicate chemotherapy for cancers; selecting cases at the least risk of complications to avoid unnecessary admissions safely, is a desirable objective for the children, their families and hospital services. Aims: To validate SPOG 2003 and Alexander guidelines for febrile children (one fever spike >38.5°C or two >38°C) on cancer chemotherapy in an audit dataset of febrile patients (n = 202), presenting to a primary treatment centre, recording outcome criteria including "one hour door to antibiotics time", non-severe events (NSE) and severe events (SE) and duration of hospital stay. Results: 202 children with leukaemia, solid tumours and brain tumours had febrile admissions, 60% presenting to the out of hours team. 55 of 96 (57%) neutropaenic patients (<.05 × 10 9 /L) breached the one hour door to antibiotic time, the majority (47, 85%) whilst awaiting blood results. In the neutropaenic group there were 43 (45%) NSEs and 2 (2%) SEs. In the non-neutropaenic group there were 36 (34%) NSEs and 2 (2%) SEs. The median length of stay of neutropaenic and non-neutropaenic groups were 5 (mean 3.3; range 0–28 days) and 2 days (mean 3.6; 0–16 days), respectively. In applying the Alexander and SPOG 2003 risk stratification criteria, an analysis of duration of stay was not performed, as the rules were not in use. The Alexander criteria identified three groups; low risk at admission and at 48 h (LR-LR), low risk at admission and standard risk at 48 h (LR-SR), or standard risk from presentation (SR). The SPOG 2003 rule identified low and standard risk patients between 8–24 h of admission. The results are presented (Table 1 ). Conclusion: Neutropaenia alone is a poor discriminator for risk stratification of febrile events in this patient group. The Alexander and SPOG 2003 risk criteria for LR predicted patients without SEs. The SPOG system's single assessment makes it applicable to the time of emergency assessment. The Alexander system lends itself to ongoing assessment of patients for early discharge. These systems would support the out of hours team in making complex judgement in this vulnerable patient group.